Strategi Pemasaran Ohana Enterprise dalam Meningkatkan Penjualan Paket Wedding Tahun 2023 - Diah Widiargun; Alamsyah Alamsyah; Ari Suseno; Mochammad Mirza (Institut Agama Islam Sunan Giri Ponorogo, 2024)
In developing a business in the wedding sector, Ohana Enterprise has created several wedding packages for brides-to-be who want to celebrate their wedding festively and efficiently. Researchers use the Observation study method and interviews. using qualitative descriptive data analysis techniques which will be analyzed using the 4P variable marketing mix strategy, price, place, product and promotion. With the aim of knowing the marketing strategies used in increasing sales of wedding packages in 2023. Based on the research that has been done, Ohana Enterprise offers wedding package prices depending on the type of options provided to increase sales of wedding packages at Ohana Enterprise in 2023 can be adjusted to client requests and the flexibility of the prices offered, the choice of venues provided is more than 50 venues, active promotion through social media content, Ohana Enterprise which has branches in various places, event and marketing teams that are actively involved in marketing carried out until the event takes place.